The new camp cookbook - Ly, Linda, 1980- (Voyager Press an imprint of The Quarto Group, 2017)
Good food makes for great camping! The two can and should go hand in hand, and the recipes and tips in this book will guide you along the way. This is a book for day trippers, adventurers, campers, and anyone who enjoys cooking outdoors. You'll find organizational advice and cooking techniques, from planning your meals, packing a cooler, and stocking a camp pantry to building a fire, grilling in foil packs, and maintaining heat in a dutch oven. The recipes are presented by meal: breakfast, lunch, snacks, sweets, and all-out feasts. You can choose your own adventure for each occasion, with recipes as easy as Mexican Street Corn Salad and Tin Foil Seafood Boil to more involved dishes like Korean Flank Steak with Sriracha-Pickled Cucumbers and Dutch Oven Deep-Dish Soppressata and Fennel Pizza. All recipes use a standard set of cookware to streamline your cooking in camp, and are marked with icons to help you quickly find a suitable recipe for your cooking style. --Publisher.